Investigations on the Redox Characteristics and Hydrogen Evolution Efficiencies of Pd and Mo Deposited Pd Electrodes in Alkaline Electrolyte (Bangladesh Journal of Scientific and Industrial Research, 2008)
Redox behaviors and hydrogen evolution efficiencies of Pd and Mo deposited Pd electrodes have been investigated in 30wt.% KOH electrolyte by cyclic voltammetry. Cyclic voltammograms of Pd electrode in between the potential range - 1.05 V to + 0.75 V showed two couples of redox peaks for the transformations of Pd(0) ←→ Pd(OH)2 and Pd(OH)2 ←→ PdOOH, an anodic peak for the desorption of diffusional hydrogen (dH) and hydrogen and oxygen evolutions at the terminal potential regions. Hydrogen evolution efficiency found decreased with time and then reached to a stable condition after 35 minutes. In presence of deposited Mo, the electrode stable condition appeared after 10 minutes only. Pd found predominates over deposited Mo. Both the Pd(0) ←Pd(OH)2 and Mo(0) ← Mo(OH)2 transformations appeared at the same potential value. Mo stopped the movement of hydrogen adsorption and absorption region of Pd electrode towards negative potential direction. It increased the hydrogen evolution efficiency of Pd electrode remarkably. At the potentials - 1.1 V, - 1.2 V, - 1.25 V and - 1.3 V, currents for Pd + Mo system found 1.44, 1.25, 1.20, 1.23 times higher than those of Pd electrode. Mo also showed hydrogen migratory role to the fraction of Pd surface covered by it. Hydrogen evolution reactions (HER) over Pd and Pd + Mo surfaces seemed followed similar mechanisms. Tafel plots for the HER for both the systems showed two Tafel regions. Exchange current density values (io) for the low and high overpotential regions of Pd + Mo system showed 2.85 times and 1.29 times higher values than those of Pd electrode. Key words: Pd, Pd-Mo, Hydrogen evolution efficiency, Hydrogen evolution reactions (HER) DOI: 10.3329.bjsir.v43i1.861 Bangladesh J. Sci. Ind. Res. 43(1), 103-116, 2008